2012
DOI: 10.1016/j.molcel.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

VE-Cadherin Signaling Induces EB3 Phosphorylation to Suppress Microtubule Growth and Assemble Adherens Junctions

Abstract: Summary Vascular Endothelial (VE)-cadherin homophilic adhesion controls endothelial barrier permeability through assembly of adherens junctions (AJs). We observed that loss of VE-cadherin-mediated adhesion induced the activation of Src and phospholipase C (PLC)γ2, which mediated Ca2+ release from endoplasmic reticulum (ER) stores resulting in activation of calcineurin (CaN), a Ca2+-dependent phosphatase. Downregulation of CaN activity induced phosphorylation of serine 162 in End Binding (EB) protein 3. This ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 62 publications
7
61
1
Order By: Relevance
“…Our results support the hypothesis that the reduced MT dynamics at N-cadherin-mediated contacts results from an inhibitory action of N-cadherin engagement, rather than from the absence of a positive signal provided by integrins, as reported for VE-cadherin engagement (Komarova et al, 2012). Indeed, the reduction of MT growth rate can be alleviated by the expression of a truncated form of N-cadherin, which interferes with the function of this protein by sequestering catenins and thus destabilizing cadherin adhesion complexes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results support the hypothesis that the reduced MT dynamics at N-cadherin-mediated contacts results from an inhibitory action of N-cadherin engagement, rather than from the absence of a positive signal provided by integrins, as reported for VE-cadherin engagement (Komarova et al, 2012). Indeed, the reduction of MT growth rate can be alleviated by the expression of a truncated form of N-cadherin, which interferes with the function of this protein by sequestering catenins and thus destabilizing cadherin adhesion complexes.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, cell-cell contact morphology, dynamics and stability are very different in epithelial and myogenic cells, the former presenting a fibroblastic phenotype with poorly differentiated cell-cell contacts that are devoid of true adherens junctions (Mège et al, 2006). By contrast, a negative-feedback loop has also been reported very recently between vascular-endothelial (VE)-cadherin-mediated contacts and MT growth in endothelial cells (Komarova et al, 2012). In addition, we observed that MTs were also repelled from cadherin adhesions formed by epithelial MDCK cells on an E-cadherin-Fc substrate.…”
Section: Discussionsupporting
confidence: 56%
“…146 They can form homo-or heterodimers. 147 Komarova et al 148 recently identified a key role of EB3 in regulating AJs adhesion by stabilizing MTs. They showed that phosphorylation of EB3 at S162 induced MT growth in confluent endothelial monolayers, which disassembled AJs.…”
Section: Role Of End-binding Proteinsmentioning
confidence: 99%
“…Images were acquired every 3 s. Microtubule growth was analyzed using a plusTipTracker software package on 55-65 frames (Matov et al, 2010). Tracking control parameters were as described previously (Komarova et al, 2012). The 'Quadrant Scatter Plot' tool, a part of plusTipTracker package, was used to determine the relationship between growth rate and growth lifetime and to divide microtubules into four subpopulations based on deviation from mean growth speed and growth lifetime (Applegate et al, 2011).…”
Section: Microtubule Dynamicsmentioning
confidence: 99%